Strategi Guru dalam Pembentukan Perilaku Anak sesuai Nilai Agama dan Moral di Kelompok B di TK Negeri 01 Al-Icmi - Candra Moahu; Rapi Us Djuko; Sulasty Ningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe in depth the teacher's strategy in shaping children's behavior according to religious and moral values ​​in Group B at TK Negeri 01 Al-Icmi, PaguyamanPantai District, Boalemo Regency. The study used a qualitative research method. The subjects of this study were twelve children in Group B and one teacher of Group B at TK Negeri 01 Al-Icmi, PaguyamanPantai District, Boalemo Regency. Data were collected through interviews and documentation. Data analysis was carried out by data editing, data presentation, and conclusions. The results of the study indicate that the implementation of the strategy has been carried out optimally. Teachers act as good role models through positive behaviors demonstrated every day, such as getting children into the habit of washing their hands before eating, praying together, and maintaining politeness and mutual respect. These habits are not only imitated by students, but also become part of the school routine that supports the development of children's religious and moral values. In addition, the teacher's behavior formation strategy uses several methods, including storytelling, singing, habituation, and role models that are adapted to the characteristics of early childhood development. This method is applied both in daily routine activities and special programs aimed at strengthening children's understanding of religious and moral values.